Writing the Great War francophone and anglophone poetics = Comment écrire la Grande Guerre? : poétiques francophones et anglophones - Bianchi, Nicolas 1990-; Garfitt, Toby (Romanticism and after in France, 2017)
For France the First World War, or Great War, was a war of national self-defence, but for Britain it was not. Does that mean that French literary treatments of this unimaginably destructive war were very different from British ones? Not necessarily – but much can be learned from considering both traditions side by side, something that is rarely done. The essays collected in this bilingual volume, by a range of scholars working on literature and history on both sides of the Channel, show that while the wider purposes of the war are striking for their absence in both French and British traditions, there are many common strands: realistic narratives of the trenches, humour as a safety-valve, imagination and creativity. Yet there are differences, too: for instance, there is plenty of French poetry about the war, but no real equivalent of the British «war poets».